Book Reviews - Mark Nichols; Ken Stevens; Andrew Higgins (Flexible Learning Association of New Zealand, 2012)
Reviews of Brabazon, T. (2002). Digital hemlock: Internet education and the poisoning of teaching. Sydney, Australia: University of New South Wales Press   Paechter, C., Edwards, R., Harrison, R., & Twining, P. (Eds.) (2001). Learning, space, and identity. London: Paul Chapman Publishing, in association with The Open University  Perraton, H., & Lentell, H. (Eds.) (2004). Policy for open and distance learning. London: RoutledgeFalmer/ Commonwealth of Learning